Newcomers to Canada: Assessing a Civil Right of Action in Canadian Courts for Crimes Against Humanity and Aggression Committed Abroad - Nestico-Semianiw, Spencer (McGill Law Journal / Revue de droit de McGill, 2025)
Many new arrivals to Canada are victims of international crimes perpetrated by states and their agents. This article considers the reception of international law in Canada to determine whether a civil right of action exists for two crimes: crimes against humanity and the crime of aggression. It also proposes recommendations that would help remove barriers for civil redress and pave the way for victims to receive reparation orders in Canadian courts for their harm. This article is a novel addition to the subject of civil remedies in Canada for breaches of international law. While much has been written on the jurisdiction of Canadian courts to prosecute crimes at international law, the scholarship on civil remedies for such crimes is scant and outdated. This article fills this gap and proposes changes to the law in order to bring Canada more closely in line with its reputation for defending human rights on the world stage.